A 12-week lifestyle intervention for middle-aged, overweight men who are supporters of local sporting clubs. (14th June 2013) - Sealey, Rebecca Maree; Twomey, Julie; Pringle, Fiona Alyce; Cheffins, Tracy; Gupta, Smita
Abstract: Objective : To evaluate the effectiveness of a 12-week lifestyle program for changes in healthy lifestyle knowledge, health perceptions and body composition of middle-aged, overweight men. Methods : A participatory, action-based experimental design was employed with a convenience sample ( n = 24) of middle-aged men who were supporters of either a local rugby league or rugby union club. Participants attended an introductory session and baseline testing in week one, participated in once-weekly group circuit exercise and lifestyle education sessions for 10 weeks and attended post-testing and project evaluation in week 12. Results : Fourteen participants completed the project. Healthy lifestyle knowledge did not improve significantly. As a combined group there were significant improvements in both physical and mental components of the SF12 questionnaire and in waist girth. The rugby league cohort achieved significant improvement in the SF12 physical component, weight, BMI and waist girth. The rugby union cohort achieved significant improvement in the SF12 mental component and waist girth. Participants reported a variety of health improvement and lifestyle changes following the project and reported appreciation at the involvement of the sporting club. Conclusions : The men's lifestyle program resulted in significant improvement in body composition, resulting in a reduction in obesity-related disease risk in some participants.